IS LIGHT READING ENOUGH TO FULLY ACQUIRE ACADEMIC LANGUAGE? THE BRIDGE HYPOTHESIS - Stephen D. Krashen (Universitas Katolik Indonesia Atma Jaya, 2010)
The Bridge Hypothesis states that pleasure reading acts as a bridge between conversational and academic language, providing the competence that makes demanding texts more comprehensible. In two studies, D. Gardner argues that pleasure reading does not play a role in helping children understand academic texts, but a close look at the data shows that Gardner's evidence actually supports the Bridge Hypothesis. Keywords: Light reading, pleasure reading, academic language, vocabulary development.